Enhanced mechanical, thermal, and UV-shielding properties of poly(vinyl alcohol)/metal–organic framework nanocomposites. Issue 67 (16th November 2018) - Dai, Yibo; Tang, Qun; Zhang, Ziang; Yu, Caili; Li, Heping; Xu, Lin; Zhang, Shufen; Zou, Zhiming
Abstract : PVA/HKUST-1 nanocomposites prepared by a simple solution casting method displayed significantly enhanced thermal stability, mechanical and UV-shielding properties. Abstract : Metal–organic framework (HKUST-1) nanoparticles were successfully synthesized, and poly(vinyl alcohol) (PVA)/HKUST-1 nanocomposite films were fabricated by a simple solution casting method. Our results showed that the addition of HKUST-1 caused a remarkable enhancement in both thermal stability and mechanical properties of the PVA nanocomposites, due to the homogeneous distribution of HKUST-1 and the strong interfacial interactions between PVA and HKUST-1. With incorporation of 2 wt% HKUST-1, the degradation temperature of the nanocomposites was about 33 °C higher than that of pure PVA. At the same time, the Young's modulus and tensile strength of the nanocomposites was approximately 137% and 32% higher than those of pure PVA, respectively. Moreover, the PVA/HKUST-1 nanocomposites also showed strikingly enhanced UV-shielding ability as well as satisfactory visible light transmittance, which revealed that HKUST-1 nanoparticles could act as a good UV absorber in nanocomposites. This work provides a novel and simple method for producing UV-shielding materials with simultaneously enhanced thermal and mechanical properties, which have potential applications in UV protection areas.